2020
DOI: 10.3390/f11111196
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of American Chestnut (Castanea dentata (Marsh.) Borkh) Using RITA® Temporary Immersion Bioreactors and We Vitro Containers

Abstract: American chestnut (Castanea dentata (Marsh.) Borkh) was almost completely wiped out by the fungal pathogen, Cryphonectria parasitica (Murrill) M.E. Barr. Another invasive pathogen, Phytophthora cinnamomi Rands, is devastating American chestnuts in the southern region of the United States. An alternative approach for controlling these pathogens is to use genetic engineering or gene editing. We successfully transformed American chestnut with a detoxifying enzyme, oxalate oxidase, to enhance blight tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The win3.12‐OxO vector (Figure 1) was constructed with the win3.12 promoter from poplar and the oxalate oxidase ( OxO ) gene from wheat and transformed into American chestnut somatic embryos (McGuigan et al, 2020). Twenty‐two independent transgenic embryo lines were recovered and tested for insert copy number using quantitative PCR (qPCR).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The win3.12‐OxO vector (Figure 1) was constructed with the win3.12 promoter from poplar and the oxalate oxidase ( OxO ) gene from wheat and transformed into American chestnut somatic embryos (McGuigan et al, 2020). Twenty‐two independent transgenic embryo lines were recovered and tested for insert copy number using quantitative PCR (qPCR).…”
Section: Resultsmentioning
confidence: 99%
“…Somatic embryos from the wild‐type C. dentata ‘Ellis 1’ (Ellis) clonal line were used for Agrobacterium‐ mediated transformation (McGuigan et al, 2020; Polin et al, 2006; Zhang et al, 2011). Somatic embryos were co‐cultivated with Agrobacterium containing the pwin3.12‐OxO vector and all transformed embryos were selected using paromomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cucumber transgenic plants overproducing the Gnk2-1 gene have displayed resistance to Fusarium oxysporum [ 34 ]. McGuigan et al [ 35 ] were recently successful in overexpressing the Cast_Gnk2-like gene in American chestnut somatic embryos, but the tolerance of transgenic plants to P. cinnamomi has not yet been checked.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that the root rot resistance locus PaLAR3B is successfully delivered from elite Norway spruce parent trees to their SE progeny through the SE-propagation method and there is no trade-off between root rot resistance locus PaLAR3B and somatic embryo production ability. McGuigan et al [7] used SE in combination with genetic transformation to confer resistance to Cryphonectria parasitica and P. cinnamomi in American chestnut. Somatic embryos were successfully transformed with a detoxifying enzyme, oxalate oxidase, to enhance blight tolerance, or with the Cast_Gnk2-like gene, which encodes for an antifungal protein, to be tested for putative tolerance to P. cinnamomi.…”
mentioning
confidence: 99%